Social Regulation of Consumer Risks in Present Conditions - ВасиленкоОльга Викторовна (Journal of Economic Sociology, 2010)
The paper is devoted to consumer risks resulted from the consumer choice of food and non-food goods and services. Consumer risk is considered as a probability for a partial loss of human potential (health, emotional balance, money) which may occur after a non-reflexive purchasing behavior. Consumer risks fall into four interconnected models which are likely to emerge at all stages of consumer choice. The paper presents outcomes of an empirical research of consumer risks in Volgograd region. It examines mechanisms of social regulation of consumer risks, including consumption culture, formation of partnerships between market actors, construction of information and communicative environment.